Estimate of incidence and cost of recreational waterborne illness on United States surface waters - Stephanie DeFlorio-Barker; Coady Wing; Rachael M. Jones; Samuel Dorevitch (BMC, 2018)
Abstract Background Activities such as swimming, paddling, motor-boating, and fishing are relatively common on US surface waters. Water recreators have a higher rate of acute gastrointestinal illness, along with other illnesses including respiratory, ear, eye, and skin symptoms, compared to non-water recreators. The quantity and costs of such illnesses are unknown on a national scale. Methods Recreational waterborne illness incidence and severity were estimated using data from prospective cohort studies of water recreation, reports of recreational waterborne disease outbreaks, and national water recreation statistics. Costs associated with medication use, healthcare provider visits, emergency department (ED) visits, hospitalizations, lost productivity, long-term sequelae, and mortality were aggregated. Results An estimated 4 billion surface water recreation events occur annually, resulting in an estimated 90 million illnesses nationwide and costs of $2.2- $3.7 billion annually (central 90% of values). Illnesses of moderate severity (visit to a health care provider or ED) were responsible for over 65% of the economic burden (central 90% of values: $1.4- $2.4 billion); severe illnesses (result in hospitalization or death) were responsible for approximately 8% of the total economic burden (central 90% of values: $108- $614 million). Conclusion Recreational waterborne illnesses are associated with a substantial economic burden. These findings may be useful in cost-benefit analysis for water quality improvement and other risk reduction initiatives.